2017
DOI: 10.1080/15374416.2017.1359787
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Origins of Rumination in Middle Childhood: The Roles of Early Temperament and Positive Parenting

Abstract: Rumination, a thinking style characterized by a repetitive inward focus on negative cognitions, has been linked to internalizing disorders, particularly depression. Moreover, research suggests that rumination may be a cognitive vulnerability that predisposes individuals to psychopathology. Surprisingly little is known, however, about the etiology and development of rumination. The present study examined the role of specific components of child temperamental negative emotionality (sadness, fear, anger) and effo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 91 publications
(136 reference statements)
2
10
0
Order By: Relevance
“…First, we found that the proximal psychological variables (i.e., Resilience, Afraid, Concentration, Rumination, and Anger) have the highest bridge strengths in the current adolescent psychosocial network, serving as bridge symptoms connecting clusters of parenting styles and psychological variables. This observed relationship is consistent with previous longitudinal and meta-analytic ndings on the association between adolescents' emotional, cognitive, and behavioral problems and negative parenting styles [44,45], It is acknowledged that parenting styles exert profound effects on shaping psychological development in childhood and adolescence [46,47], and adolescents tend to respond with dysfunctional emotion or negative behavior when their emotional needs are not met by their parents during this critical and challenging period [48], Thus, negative parenting styles act as a factor that increases the activation of rumination, anxiety, and depression and decreases adolescents' resilience through the psychosocial network. However, further studies are needed to determine a causal relationship among the aforementioned factors.…”
Section: Discussionsupporting
confidence: 91%
“…First, we found that the proximal psychological variables (i.e., Resilience, Afraid, Concentration, Rumination, and Anger) have the highest bridge strengths in the current adolescent psychosocial network, serving as bridge symptoms connecting clusters of parenting styles and psychological variables. This observed relationship is consistent with previous longitudinal and meta-analytic ndings on the association between adolescents' emotional, cognitive, and behavioral problems and negative parenting styles [44,45], It is acknowledged that parenting styles exert profound effects on shaping psychological development in childhood and adolescence [46,47], and adolescents tend to respond with dysfunctional emotion or negative behavior when their emotional needs are not met by their parents during this critical and challenging period [48], Thus, negative parenting styles act as a factor that increases the activation of rumination, anxiety, and depression and decreases adolescents' resilience through the psychosocial network. However, further studies are needed to determine a causal relationship among the aforementioned factors.…”
Section: Discussionsupporting
confidence: 91%
“…This is unsurprising given the shared valence of these two constructs. The relatively stronger association between sadness and FC (compared with PE and FC) may be related to rumination given that rumination has been found to be associated with both early NE (Schweizer et al, 2018) and altered neural patterns during negative-emotion processing (Mandell et al, 2014). Although the paradigm used in this study did not tap into ruminative processes, future studies that directly measure rumination will help illuminate the relationships between early temperament, rumination, and brain function subserving emotion processing.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies on pre-adolescents [ 36 ] and late adolescents [ 37 ] did not find support for an association between inhibition and rumination. Findings from another community-sampled study indicated that inhibitory control weakness at age 3 was predictive of elevated rumination levels at age 9, but only in the context of having a highly angry temperament in early childhood [ 38 ]. In one adolescent community sample, rumination was associated with inhibition weakness during an emotional Go/No-Go task, especially in response to negative information when shifting from negative to positive stimuli, but not during a non-affective task assessing inhibition [ 39 ].…”
Section: Models Of Inhibition and Ruminationmentioning
confidence: 99%
“…In Olson et al’s (1992) Circumplex Model of family systems, healthy family functioning encompasses a positive communication style, balanced levels of cohesion or the emotional bond between family members, and adaptability in a family when facing a stressor [ 55 ]. One study found that children with poor IC ruminated less if they had parents who displayed positive communication and interaction styles compared to children whose parents displayed negative communication styles [ 38 ]. However, the overall lack of research on the associations among CM, family support, rumination, and IC in adolescence presents a missed opportunity for research on vulnerability factors for depression.…”
Section: Environmental Factorsmentioning
confidence: 99%